Wind energy as an alternative source of electricity - Melnychenko, Igor; Diachenko, G. G.; Hubkina, V. V. (My University, 2021)
In modern Ukraine, a large amount of electricity is restored from nonrenewable sources. (gas, coal, oil, uranium). According to experts, the reserves of these energy resources will last for another 40-100 years. Every year they are mined in increasingly hard-to-reach places. Therefore, their extraction becomes more expensive and the economic efficiency of the use of fossil fuels is rapidly declining. Humanity, already faced with an energy crisis, is trying to find new, environmentally friendly, and renewable sources of electricity, more profitable in terms of cheapness and transportation.
Keywords: wind energy; alternative energy; green energy